ANALISIS BREAK EVENT POINT PADA USAHA TERNAK KERBAU BELANG DI TORAJA - Pabisangan, Valent; Idris, Hariany; Idrus, mukhammad (Universitas Jabal Ghafur, 2024)
This research aims to determine the break event point analysis in the striped buffalo farming business in Toraja. Data collection techniques were carried out using interviews and documentation. The data analysis technique used is qualitative descriptive analysis, namely by analyzing facts found in the field, then connecting them with the theories obtained by the author in analyzing break event points. Based on the results of research on break event point analysis in striped buffalo farming businesses in Toraja, the researchers concluded that the break event point analysis in striped buffalo farming businesses cannot be calculated based on the BEP formula. Cost analysis shows that the costs incurred in the buffalo farming business include: Initial capital, feed costs, maintenance costs, operational costs, vitamin and worming costs. Analysis of selling prices shows that the price of striped buffalo is influenced by general factors, but what will determine is the type of buffalo and an assessment of the meaning of social symbols inherent in Toraja society. The striped buffalo farming business has very worthy potential to be developed because it can promise quite large income or profits.